Phosphorylation and activation of the Xenopus Cdc25 phosphatase in the absence of Cdc2 and Cdk2 kinase activity. - Izumi, T (1995)
The M-phase inducer, Cdc25C, is a dual-specificity phosphatase that directly phosphorylates and activates the cyclin B/Cdc2 kinase complex, leading to initiation of mitosis. Cdc25 itself is activated at the G2/M transition by phosphorylation on serine and threonine residues. Previously, it was demonstrated that Cdc2 kinase is capable of phosphorylating and activating Cdc25, suggesting the existence of a positive feedback loop. In the present study, kinases other than Cdc2 that can phosphorylate and activate Cdc25 were investigated. Cdc25 was found to be phosphorylated and activated by cyclin A/Cdk2 and cyclin E/Cdk2 in vitro. However, in interphase Xenopus egg extracts with no detectable Cdc2 and Cdk2, treatment with the phosphatase inhibitor microcystin activated a distinct kinase that could phosphorylate and activate Cdc25. Microcystin also induced other mitotic phenomena such as chromosome condensation and nuclear envelope breakdown in extracts containing less than 5% of the mitotic level of Cdc2 kinase activity. These findings implicate a kinase other than Cdc2 and Cdk2 that may initially activate Cdc25 in vivo and suggest that this kinase may also phosphorylate M-phase substrates even in the absence of Cdc2 kinase.